Battery-free, skin-interfaced microfluidic/electronic systems for simultaneous electrochemical, colorimetric, and volumetric analysis of sweat - Bandodkar, Amay J.; Gutruf, Philipp; Choi, Jungil; Lee, Kun Hyuck; Sekine, Yurina; Reeder, Jonathan T.; Jeang, William J.; Aranyosi, Alexander J.; Lee, Stephen P.; Model, Jeffrey B.; Ghaffari, Roozbeh; Su, Chun Ju; et al. (Science Advances, 2019)
Wearable sweat sensors rely either on electronics for electrochemical detection or on colorimetry for visual readout. Non-ideal form factors represent disadvantages of the former, while semiquantitative operation and narrow scope of measurable biomarkers characterize the latter. Here, we introduce a battery-free, wireless electronic sensing platform inspired by biofuel cells that integrates chronometric microfluidic platforms with embedded colorimetric assays. The resulting sensors combine advantages of electronic and microfluidic functionality in a platform that is significantly lighter, cheaper, and smaller than alternatives. A demonstration device simultaneously monitors sweat rate/loss, pH, lactate, glucose, and chloride. Systematic studies of the electronics, microfluidics, and integration schemes establish the key design considerations and performance attributes. Two-day human trials that compare concentrations of glucose and lactate in sweat and blood suggest a potential basis for noninvasive, semi-quantitative tracking of physiological status.
Keywords: Colorimetric assays; Design considerations; ELectrochemical detection; Electronic sensing; Integration scheme; Microfluidic platforms; Physiological status; Systematic study; Bioelectric Energy Sources; Biosensing Techniques; Chlorides; Colorimetry; Glucose; Healthy Volunteers; Humans; Hydrogen-Ion Concentration; Lab-On-A-Chip Devices; Lactic Acid; Male; Microfluidics; Skin; Sweat; Wearable Electronic Devices